Exosome-Shuttled circSHOC2 from IPASs Regulates Neuronal Autophagy and Ameliorates Ischemic Brain Injury via the miR-7670-3p/SIRT1 Axis - Wanghao Chen; Hong Wang; Zhihan Zhu; Jia Feng; Lukui Chen (Elsevier, 2020)
The aim of the present study was to investigate the neuroprotective roles and mechanisms of the circular RNA circSHOC2 in ischemic-preconditioned astrocyte-derived exosomes (IPAS-EXOs) against ischemic stroke. We established an ischemia model based on oxygen glucose deprivation (OGD) in vitro and isolated resultant exosomes from astrocytes. Neuronal viability and apoptosis were determined by Cell Counting Kit-8 (CCK-8) assays and TUNEL (terminal deoxynucleotidyltransferase-mediated deoxyuridine triphosphate nick end labeling) staining, respectively. Autophagy-related proteins were analyzed by western blotting. We found that exosomes derived from IPAS-preconditioned medium (IPAS-CM) exerted neuroprotection. Furthermore, circSHOC2 expression was significantly upregulated in exosomes released from IPAS-CM. Overexpression of circSHOC2 in neurons yielded the same protective effects as those from IPAS-EXOs in vitro, and similar results were also observed in the middle cerebral artery occlusion (MCAO) mouse model. Mechanistically, circSHOC2 reduced neuronal apoptosis via regulating autophagy. Furthermore, circSHOC2 was found to sponge miR-7670-3p, which regulated SIRT1 expression. Transfection with an miR-7670-3p small interfering RNA (siRNA) (siRNA-7670-3p) and incubation with circSHOC2 extracellular vesicles attenuated ischemia-induced neuronal apoptosis in vivo and in vitro, while silencing of SIRT1 reversed the protective effects of exosomal circSHOC2 on hypoxic cerebral neurons. Taken together, our findings indicate that circSHOC2 in IPAS-EXOs suppressed neuronal apoptosis and ameliorated neuronal damage by regulating autophagy and acting on the miR-7670-3p/SIRT1 axis, which might contribute to a therapeutic strategy for ischemic stroke treatment.